Toxicity of The Dried Parts of Pulicaria crispa Herb (Tagar) on Lymnaea cailludi, Anopheline larvae, Oreochromis niloticus Fingerlings And Tadpoles: الآثار السامة للأعضاء الجافة لنبات التقر على قواقع ليمنيا كايودى ويرقات بعوض الأنوفليس وأصبعيات سمك البلطى وصغار الضفادع - El Hassan, Somia Abdalla Mohammed (Journal of Faculty of Education, 2021)
The toxicity evaluation and molluscicidal activity of the dried parts of pulicaria crispa( leaves, flowers and stems) was tested against Lymnaea cailludi adult snails" the intermediate host of Fasicioliasis" and non – target organisms (Anopheline larvae, fingerlings fishes and tadpoles). The plant was collected from Shambat area, air dried under shade and ground to powder, then used in different concentrations. The assessment of the plant activity was based on calculating the doses for 50% and 95% of the animals tested (LD50 and LD95). Dried leaves showed high molluscicidal potency against Lymnaea cailludi snails and tadpoles, low activity against Anopheline larvae and without toxic effect against fingerling fishes, Dried flowers have shown high toxicity against the tadpoles, low toxicity against the snails and Anopheline larvae and no toxicity against fishes. Dried stems have shown low toxicity against the snails, Anopheline larvae and tadpoles with no toxicity against fishes